1988
DOI: 10.1016/0014-5793(88)81243-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the D1 protein in a photosystem II mutant (LF‐1) of Scenedesmus obliquus blocked on the oxidising side Evidence supporting non‐processing of D1 as the cause of the lesion

Abstract: The DI polypeptide of the photosystem II reaction centre in a mutant (LF-I) of Scenedesmus obliquus lacking a watersplitting manganese complex is approx. 1.5 kDa larger than that in the wild type but the D2 protein is the same size.The peptide profiles of DI on partial digestion with papain or endoproteinase Lys-C indicate that the extra segment in the LF-I protein is located at or near the carboxyl-terminus.The Dl proteins produced by in vitro translation of mRNA from wild type and LF-I cells have an identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 37 publications
(2 reference statements)
0
19
0
Order By: Relevance
“…Moreover, LF-1 was undamaged on the reducing side of PS II, contained a functional reaction center, and displayed active secondary donor function (Metz et al 1985, Rutherford et al 1988. Several groups have suggested that the mutant inserts a D 1 protein with an unprocessed carboxyl end (Metz et al 1986, Diner et al 1988, Taylor et al 1988a. Apparently the unprocessed D1 protein renders the mutant unable to bind at least some functional Mn and hence inhibits its ability to evolve 02.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LF-1 was undamaged on the reducing side of PS II, contained a functional reaction center, and displayed active secondary donor function (Metz et al 1985, Rutherford et al 1988. Several groups have suggested that the mutant inserts a D 1 protein with an unprocessed carboxyl end (Metz et al 1986, Diner et al 1988, Taylor et al 1988a. Apparently the unprocessed D1 protein renders the mutant unable to bind at least some functional Mn and hence inhibits its ability to evolve 02.…”
Section: Introductionmentioning
confidence: 99%
“…The LF-l PS II had active electron acceptor functions and contained a reaction center functional in electron transport, as characterized by the EPR spectra of radicals fonned upon illumination . The defective protein was identified as the Dl protein of PS II (Metz et al, 1986;Taylor et al, 1988), while the D2 protein was apparently unchanged from its WT counterpart (Taylor et al, 1988). The Dl protein was shown to function on both the oxidizing and reducing sides of PS II, providing the first experimental evidence that D 1 is a reaction ~enter protein (Metz et al, 1986).…”
mentioning
confidence: 82%
“…The Dl protein was shown to function on both the oxidizing and reducing sides of PS II, providing the first experimental evidence that D 1 is a reaction ~enter protein (Metz et al, 1986). This D 1 protein has been proposed to assemble into PS II without proper processing of the carboxyl end (Metz et al, 1986;Diner et al, 1988;Taylor et al, 1988) which somehow blocks incorporation of the full complement of Mn required for oxygen evolution. These characteristics of the LF-l mutant provide further evidence for Mn-binding in the region near the carboxy I end of the D 1 protein.…”
mentioning
confidence: 99%
“…One of many unusual features of the D1 protein is its carboxy-terminal processing after being translated on chloroplast ribosomes as a precursor protein [7,9,16,19]. Studies with the LF-1 mutant of Scenedesmus obliquus have shown that removal of the oligopeptide extension by a protease is essential for the assembly of a functional oxygen-evolving complex [4,24]. In spinach the processing site is located at an alanine residue in position 344, resulting in the removal of a peptide segment containing 9 amino acids [22,23].…”
Section: Introductionmentioning
confidence: 99%